Influence of salinity, temperature and dissolved oxygen on embryonic development of the South West African pilchard, Sardinops ocellata - King, David P. F.(David Patrick Francis) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1975.